Study of the Implementation of Online Biology Teaching at SMAN 06 Merangin during the Pandemic Period - Ayu Andriyanti; Heffi Alberida (Master Program of Biology Education, Universitas Lambung Mangkurat, 2021)
The impact of the Covid-19 pandemic is felt in various sectors, including education, so that learning activities are limited by implementing online learning. Likewise with SMAN 06 Merangin. This study aims to obtain an overview of the implementation of online biology learning at SMAN 06 Merangin. The subject of this research is a biology teacher. Data was collected using interviews. Data analysis was performed using the Miles & Huberman analysis technique. The results of research on the implementation of blood-based biology learning at SMAN 06 Merangin show that (1) the lesson planning is carried out, namely: determining the application, recording conditions and student phone numbers, preparing online learning tools; (2) implementation of online learning, namely preliminary activities in the form of filling in attendance via Google Form, Google Classroom or Whatsapp and submitting learning objectives to Google Classroom or Whatsapp. The core activities are in the form of delivering material, question and answer sessions via Classroom or Whatsapp. Closing activities in the form of drawing conclusions and assignments; (3) evaluations of online learning, namely, assessment of knowledge seen from the results of assignments, discussion of questions, and online exams. Skills assessment is seen from the results of project assignments and online practicum. Meanwhile, the attitude value is seen from the presence. Weak supervision of students, lack of strong signals in remote areas, and not all students have Gadgets are obstacles in the implementation of online biology learning at SMAN 06 Merangin. AbstrakDampak pandemi Covid-19 sangat terasa pada berbagai sektor, termasuk pendidikan, sehingga pembatasan aktivitas pembelajaran dengan menerapkan pembelajaran daring. Begitu juga dengan SMAN 06 Merangin. Penelitian ini bertujuan untuk memperoleh gambaran pelaksanaan pembelajaran biologi secara daring di SMAN 06 Merangin. Subjek penelitian ini adalah guru biologi. Data dikumpulkan dengan wawancara. Analisis data dilakukan menggunakan teknik analisis Miles & Huberman. Hasil penelitian terhadap pelaksanaan pembelajaran biologi berbasis daring di SMAN 06 Merangin menunjukkan bahwa (1) Perencanaan pembelajaran yang dilakukan meliputi: menentukan aplikasi, pendataan kondisi dan nomor telepon siswa, menyiapkan perangkat pembelajaran daring; (2) pelaksanaan pembelajaran daring terdiri dari kegiatan pendahuluan berupa mengisi absensi melalui Google Form, Google Classroom atau Whatsapp dan penyampaian tujuan pembelajaran pada Google Classroom atau Whatsapp. Kegiatan inti meliputi penyampaian materi, sesi tanya jawab melalui Classroom atau Whatsapp. Kegiatan penutup berupa penarikan kesimpulan dan penugasan; (3) evaluasi pembelajaran daring meliputi, penilaian pengetahuan, keterampilan dan sikap. Nilai pengetahuan diperoleh dari penilaian tugas, diskusi dan ujian online. Nilai keterampilan diperoleh dari tugas proyek dan praktikum Online. Sedangkan nilai sikap dilihat dari presensi. Lemahnya pengawasan terhadap siswa, kurang kuatnya sinyal di daerah pelosok dan tidak semua siswa memiliki Gadget menjadi kendala dalam pelaksanaan pembelajaran biologi secara daring di SMAN 06 Merangin.